A contribuição da pós-graduação para a formação acadêmica e profissional dos egressos - Pontes, Alinildo Ferreira de (2023)
Monitoring graduates is a very current topic and of great importance for postgraduate courses. Knowing the reality of graduates contributes to the strategic planning of courses and to better training provided in postgraduate programs. The main objective of this work was to highlight the contributions that the aforementioned program provided to graduates for their insertion into the professional job market and academic career. The methodology for conducting this study is based on a qualitative approach, with descriptive and interpretative characteristics. We collected data through documents and administered a questionnaire. The population of our research comprises graduates from the first class of 2008 to those graduating in October 2022. As a result of this research, we concluded that PPGAU has been able to contribute significantly to the academic and professional careers of graduates, training and enabling resources human resources for the practice of architecture in various fields, especially for scientific research and teaching in higher education, aligned with the objectives of postgraduate studies, enabling them to continue their professional and academic lives.